Keramikken fra Lindholtgård - Bodilsen, Ann (Hikuin, 2001)
Earthenware from Lindholtgård By Ann Bodilsen The majority of the earthenware stems from the waster pit or the stoke pit and is made up of misfired or discarded pottery, while in the kiln itself only single potsherds were found. The majority of the pottery was discarded because it was too softly fired, but there are also sintered and melted potsherds as a result of too intense firing. At the time of writing, 4,859 potsherds have been cleaned and numbered, which is estimated to correspond to 1/4 of the material. The presentation of the pottery material is only based on a survey of the cleaned material considered to be representative. This is not a detailed presentation but a quick review in which the most important characteristics are highlighted. Only a few vessel forms are represented in the material. The predominant forms are pitchers and pots with a rounded body and outbent rim with so-called lid grooves on the inside. But there is also a small quantity of pots only with outbent rims, shallow bowls, and a few pans. Pitchers. So far it has not been possible to gather large pieces of a pitcher. However, they seem to have been fairly uniform as far as their size is concerned, with a base diameter of between 12 and 14 cm, a rim diameter of about 10 cm and an estimated height of between 20 and 25 cm. The pitchers all had frilled flat bases shaped by finger pressure along the base edge (fig. 1). The most frequently occurring one is a frilled type with a wide, horizontally indented thumb print all the way around. The body of the pitcher is shaped almost cylindricaly from the base, but with a slight outward curve. The pitchers have a distinctly thrown rim with horizontal grooves on the neck; the body, however, seems to have been shaped by hand. There are several versions of pitcher handles (fig. 2) with a handle twisted to the right occurring most frequently. At the top the handles were attached at the opening, whereas at the bottom they are attached at the transition between neck and body. The rim profile is highly uniform with a distinct fluted moulding directly beneath the rim and beneath this a moulding. The spout of the pitcher is pulled out (fig. 3 and 4). The pitchers are richly decorated and there are both plastic and painted decorations (figs. 5-8). Only very few of the pitchers are glazed, but there is no doubt that all of the pitchers were intended to be glazed. In the cases where it is possible to observe a well-melted glaze, the color varies from yellow-green to green and brown. Pots. On the basis of the rim two types of cooking pots may be distinguished, both with outbent rims (figs. 9-10). The most common type has a strongly marked so-called lid groove on the inside, while the other is one without the so-called lid groove. The upper part of the bowl seems to be thrown. As far as size is concerned, the pots were rather uniform: the diameter of the rim varying from 19 to 26 cm – most of them measuring about 20 cm. With the exception of the pitcher bases, no flat bases were registered in the material, and it must therefore be assumed that all of the pots had a rounded body. Fragments of feet and pulled feet show that some of the pots existed in a tripod version (fig. 11). Lugs or other kinds of handles that might belong to the bowls were not found in the material. Bowls. A few sherds are definitely from bowls. These are shallow, wide bowls, 8-10 cm high and a minimum of 20 cm in diameter – all with a pronounced outbent curved rim (figs. 12-13). Pans. The only vessels of which it was possible to gather large pieces are two pans (figs. 14-15). Both pans are equipped with toes, but none of them still have a handle or lugs. Potsherds serving an unknown purpose. Single potsherds with a highly uniform appearance cannot be attributed to any of the above- mentioned kinds of vessels (figs. 16-17). These are sturdy, flat potsherds decorated with a strong, slightly arched moulding with a notch on the top. The potsherds have tentatively been interpreted as covers. Just as in the other Danish finds of potter kilns, the Lindholtgård kiln was not found in a context from which it could be dated. The dating of the kiln is thus exclusively based on the pottery material. The types of the vessels and the details of their decoration point towards the second half of the 14th century as for their dating, and with the presence of the pans the finds can probably be dated at the earliest to the years up to the year 1400. The potter in Lindholtgård most likely sold his wares in his local region. Unfortunately, there are few localities nearby with pottery material from the same period as the finds from Lindholtgaard. One locality is Sevel Skovby, not quite two kilometers from Lindholtgård. From here there is a small collection of pottery with a great number of similarities to the pitchers in the Lindholtgård material (fig. 18). The other locality is Tvis Kloster, located about 14 kilometers southwest of Lindholtgård. Here there are also many similarities to the pitchers from Lindholtgård.